The Bioactive Compounds of Avicenia sp Stem Extract Improved the Viability of Fish Challenged with Aeromonas hydrophila (SENYAWA BIOAKTIF EKSTRAK BATANG AVICENIA SP MENINGKATKAN VIABILITAS IKAN YANG DITANTANG DENGAN AEROMONAS HYDROPHILA) - Ali, Alimuddin; Dini, Iwan; Darminto, Darminto; Hartati, Hartati; Rante, Herlina (Jurnal Veteriner; Vol 19 No 3 (2018), 2018)
Aeromonas hydrophila is one of bacteria as major diseases for the Motile Aeromonads Septicemia (MAS). The aims of this research to get a substance which potential as bioactive of stems bark of Avicennia sp. for increase fish viability which exposed of A. hydropila. The samples were extracted by using ethanol 70% and then evaluated of antibacterial activities by paper disk diffusion agar technique. The active extracts were partial purified by chromatography column. The fraction of substance was show activities against bacteria analyzed by GC-MS. The results were found four peak and predicted as (1) 2-propenoic acid, 3-[3, 4-dimethoxyphenyl]-methyl ester (2) 3, 4-dimethoxycinnamic acid, (3) 1, 1-dimethyl guanidine (4), Methyl 10-oxostearate. The active fraction was isolated from stem bark of Avicennia sp. should be further studied in animal models for in vitro efficacy and toxicity. The percentage of in vivo towards test fish viabilities showed the difference between treated and untreated. The percentage of viability ranged from 35 to 83.33% while control was 91.67%. Based on finding, we suggest that Avicenia sp. bark extract was increasing of fish viability.